Acceptability of child adoption as management option for infertility in Nigeria: evidence from focus group discussions (2009)
Infertility remains a global health challenge with devastating psycho-social consequences in many African communities. Adoption that may serve as an alternative strategy for the affected couples is not widely practiced. This study was conceptualized to assess the acceptability of child adoption as a management option by Nigerians. Twelve focus group discussions were held involving three communities stratified into inner core, transitory and peripheral, within Ibadan metropolis, South-Western Nigeria from May to July 2008. The participants were purposively selected based on gender and age group. The barriers mentioned were cultural practices, stigmatization, financial implications, and procedural bottle-necks. Measures suggested to curb these negative attitudes were advocacy, community mobilization and enactment of supportive law that will protect all parties involved